Efektivitas Pendidikan Teman Sebaya terhadap Pengetahuan dan Keterampilan SADARI pada Remaja Putri dalam Deteksi Dini Kanker Payudara di SMAN Kapan - Meilisa Djami Balu; Ribka Limbu; Tasalina Y. P. Gustam (Yayasan Literasi Sains Indonesia, 2024)
One of the pillars in reducing deaths from breast cancer is health promotion for early detection. Peers have a big role for individuals in building awareness of health, especially in doing BSE as an effort to detect breast cancer early. This study aims to determine how effective peer education is on the knowledge and skills of BSE as an effort to early detection of breast cancer in adolescent girls at SMAN Kapan. This research is a Quasi Experimental research using Nonequivalent Control Group Design. The population in this study was 87 people wuth a research samples of 22 people as a treatment group and 22 people as a control group but these two groups were not randomly selected. The instruments used were questionnaires and checklist sheets. The results of the normality test showed that the data were not normally distributed so that the data analysis technique used was univariate analysis and the Independent Sample t-Test (Mann-Whitney U). The results showed that there was a significant difference in the level of knowledge (ρ-value=0.009) and skills (ρ-value=0.000) of adolescent girls at SMAN Kapan. The conclusion of this study is that peer education is effective in improving BSE knowledge and skills. Based on the results of the study, for respondents who are willing to participate, it’s hoped that they will be able to become pioneers in providing education about BSE and how to do it to their peers at school, home or in the community. In addition, further research is recommended to compare peer education methods with other simpler methods and in different populations such as at different age levels.